HEAT FLOW AND GAS HYDRATES OF THE BAIKAL RIFT ZONE - Golmshtok A.Y.; Duchkov A.D.; Hutchinson D.R.; Khanukaev S.B. (My University, 2000)
Multi-channel seismic studies (MCS), performed during a Russian expedition in 1989 and a joint Russian-American expedition in 1992, have for the first time revealed a “bottom simulating reflector” (BSR) in Lake Baikal. These data have shown that gas hydrates occur in the southern and central basins of Lake Baikal in those places where the water depth exceeds 500–700 m. Four types of tectonic influence on the distribution of the gas hydrate were revealed: (a) Modern faults displace the BSR as they do with normal seismic boundaries. (b) Older faults displace normal reflectors, whereas the BSR is not displaced. (c) Modern faults form zones, where the BSR has been totally destroyed. (4) Processes that occur within older fault zones situated close to the base of the hydrated sediment layer lead to undulations of the BSR. The thickness of the hydrate stability field (inferred from seismic data) ranges between 35 and 450 m. Heat-flow values determined from BSR data range from 48 to 119 mW/m2. A comparison between heat-flow values from BSR data and values measured directly on the lake bottom shows an overall coincidence. Changes in water level and bottom-water temperature that occurred in the past have had no noticeable influence on the present BSR depths or heat-flow values. Determination of deep heat flow from BSR data is in this case more reliable than by direct measurements.